Short and midterm functional and radiological outcomes of revision total hip arthroplasty with uncemented extensively porous coated monoblock cylindrical femoral stems - Zala, Kashyap L. (International Journal of Research in Orthopaedics, 2023)
Background: This retrospective cohort study examines clinical and radiological outcomes of revision total hip arthroplasty (THA) using uncemented extensively porous coated mono block femoral stems. Methods: Patients who were operated for revision THA at medical college Baroda, between January 2008 to December 2018, and who had at least 36 months follow up were included in the study. Details were retrieved from hospital records. Harris hip score (HHS) was used for functional outcome and Paprosky classification was used for femoral bone defects. Results: Mean age of patients was 60.1 year (range 35-86 years), mean follow up was 84 months (range 40-126 months), Paprosky type 1 defect was found in 4 hips, type 2 was found in 20 hips and type 3a defect was found in 21 hips. Mean HHS improved from pre-operative 30 to post-operative 78 (p=0.0104). Expected survival at 5 and 10 years was more than 95%. No stem was loose at the end of follow up. Thigh pain and proximal osteolysis were most common complications. Conclusions: Extensively porous coated cylindrical stems give good functional and radiological outcomes at short and midterm follow up.